Tinjauan Tentang Tugas dan Wewenang Balai Pengawas Obat dan Makanan (BPOM) di Batam Terhadap Peredaran Kosmetik Berbahan Kimia Berbahaya di Kota Batam - Alfis Setyawan; Merry Mitha Sari (Fakultas Hukum, Universitas Internasional Batam, 2019)
The purpose of this research is to find out the Duties and authorities of the Food and Drug Supervisory Agency (BPOM) in the supervision of the circulation of cosmetics made from hazardous chemicals in Batam so that it can be known the forms in the implementation of supervision and the factors that impede the supervision process carried out by the Balai POM. This research method uses a type of empirical juridical research by conducting interviews with Balai POM Officers and interviews with Business Actors and supported by the provisions of the Act relating to the supervision of the circulation of cosmetics made from hazardous chemicals which are then compared with facts that occur and analyzed descriptively. Duties and authorities obtained by the Central Bureau of Drug and Food Control directly from the Law to examine and act on distribution facilities that commit violations still do not produce public output in accordance with applicable legal regulations, there are obstacles that impede the implementation of supervision and enforcement so that they have not reached conformity between regulations and business actor behavior.